Prevalence and impact of work-related musculoskeletal disorders among food delivery riders in Eastern Peninsular Malaysia - Ahmad, Elyas; Daud, Aziah; Hairon, Suhaily; Nordin, Rusli; Azmir, Nor Azali; Md Jalil, Mohd Azlis Sani (Ijirss, 2023)
Work-related Musculoskeletal Disorders (WMSDs) are currently a matter of concern in the occupational world, where it is the leading cause of disability among workers. Food delivery riders were among the neglected workers even though they were highly exposed to the WMSDs. Thus, this study aims to quantify the magnitude of WMSDs among the riders and the impact on their work. This was a cross-sectional study involving 191 food delivery riders in Eastern Peninsular Malaysia. The Standardized Nordic Musculoskeletal Questionnaire (M-SNMQ), which was self-administered and validated for Malay translation, was used to quantify the prevalence of WMSDS based on various specific body regions. WMSD prevalence over a 12-month period was 74.9%. Upper back pain (UBP) (55.6%) and lower back pain (LBP) (73.3%) were the two most common body regions to experience WMSD symptoms. The least-complained body regions were thighs and feet, with a prevalence of 2.6% and 3.1%, respectively. The affected body regions that caused the highest daily life disturbance were the shoulders and knees, while those with shoulders symptom were more likely to be absent from work. Finally, LBP was the highest body region with at least a moderate pain score. In general, the findings should be a matter of concern among health authorities and others to improve the quality of life among the riders. To lower the prevalence of WMSDs among this understudied group, additional interventional research should be built on the findings of this study.